Odpowiedź :
(10-2½):1½ -1¾ ×(2²₇-5⁶₇) = (²⁰/₂ - ⁵/₂):³/₂ - ⁷/₄ x (¹⁶/₇ - ⁴¹/₇) =
¹⁵/₂ x ⅔ - ⁷/₄ x (-²⁵/₇) = 5 - (-¹⁷⁵/₂₈) = 5 + 6⁷/₂₈ = 11¼
2¼×(2½-2¼) = 2¼ x (⁵/₂ - ⁹/₄) = ⁹/₄ x (¹⁰/₄ - ⁹/₄) = ⁹/₄ x ¼ = ⁹/₁₆
Mam nadzieję, że pomogłam ;)
¹⁵/₂ x ⅔ - ⁷/₄ x (-²⁵/₇) = 5 - (-¹⁷⁵/₂₈) = 5 + 6⁷/₂₈ = 11¼
2¼×(2½-2¼) = 2¼ x (⁵/₂ - ⁹/₄) = ⁹/₄ x (¹⁰/₄ - ⁹/₄) = ⁹/₄ x ¼ = ⁹/₁₆
Mam nadzieję, że pomogłam ;)
Odpowiedź:
[tex](10-2\dfrac{1}{2}):1\dfrac{1}{2}-1\dfrac{3}{4}*(2\dfrac{2}{7}-5\dfrac{6}{7})=(9\dfrac{2}{2}-2\dfrac{1}{2}):\dfrac{3}{2}-\dfrac{7}{4}*(-3\dfrac{4}{7})=\\\\\\=7\dfrac{1}{2}:\dfrac{3}{2}-\dfrac{\not7^1}{4}*(-\dfrac{25}{\not7_{1}})=\dfrac{\not15^5}{\not2_{1}}*\dfrac{\not2^1}{\not3_{1}}+\dfrac{25}{4}=5+6\dfrac{1}{4}=11\dfrac{1}{4}[/tex]
[tex]2\dfrac{1}{4}*(2\dfrac{1}{2}-2\dfrac{1}{4})=\dfrac{9}{4}*(2\dfrac{2}{4}-2\dfrac{1}{4})=\dfrac{9}{4}*\dfrac{1}{4}=\dfrac{9}{16}[/tex]